A P2RX7 single nucleotide polymorphism haplotype promotes exon 7 and 8 skipping and disrupts receptor function. Issue 3 (31st January 2020) - Skarratt, Kristen K.; Gu, Ben J.; Lovelace, Michael D.; Milligan, Carol J.; Stokes, Leanne; Glover, Rachel; Petrou, Steven; Wiley, James S.; Fuller, Stephen J.
Abstract: P2X7 is an ATP‐gated membrane ion channel that is expressed by multiple cell types. Brief exposure to ATP induces the opening of a nonselective cation channel; while repeated or prolonged exposure induces formation of a transmembrane pore. This process may be partially regulated by alternative splicing of full‐length P2RX7A pre‐mRNA, producing isoforms that delete or retain functional domains. Here, we report cloning and expression of a novel P2RX7 splice variant, P2RX7L, that is, characterized by skipping of exons 7 and 8. In HEK 293 cells, expression of P2RX7L produces a protein isoform, P2X7L, that forms a heteromer with P2X7A. A haplotype defined by six single nucleotide polymorphisms (SNPs) (rs208307, rs208306, rs36144485, rs208308, rs208309, and rs373655596) promotes allele‐specific alternative splicing, increasing mRNA levels of P2RX7L and another isoform, P2RX7E, which in addition has a truncated C‐terminus. Skipping of exons 7 and 8 is predicted to delete critical amino acids in the ATP‐binding site. P2X7L‐transfected HEK 293 cells have phagocytic but not channel, pore, or membrane‐blebbing function, and double‐transfected P2X7L and P2X7A cells have reduced pore function. Heteromeric receptor complexes of P2X7A and P2X7L are predicted to have reduced numbers of ATP‐binding sites, which potentially alters receptor function compared to homomeric P2X7A complexes.